High prevalence of chronic kidney disease in a community survey of urban Bangladeshis: a cross-sectional study - Anand, Shuchi (BioMed Central, 2014)
BACKGROUND: The burden of chronic kidney disease (CKD) will rise in parallel with the growing prevalence of type two diabetes mellitus in South Asia but is understudied. Using a cross-sectional survey of adults living in a middle-income neighborhood of Dhaka, Bangladesh, we tested the hypothesis that the prevalence of CKD in this group would approach that of the U.S. and would be strongly associated with insulin resistance. METHODS: We enrolled 402 eligible adults (>30 years old) after performing a multi-stage random selection procedure. We administered a questionnaire, and collected fasting serum samples and urine samples. We used the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation to estimate glomerular filtration rate, and sex-specific cut offs for albuminuria: > 1(.)9 mg/mmol (17 mg/g) for men, and >2(.)8 mg/mmol (25 mg/g) for women. We assessed health-related quality of life using the Medical Outcomes Study Short Form-12 (SF-12). RESULTS: A total of 357 (89%) participants with serum samples comprised the analytic cohort. Mean age of was 49(.)5 (± 12(.)7) years. Chronic kidney disease was evident in 94 (26%). Of the participants with CKD, 58 (62%) had albuminuria only. A participant with insulin resistance had a 3(.)6-fold increase in odds of CKD (95% confidence interval 2(.)1 to 6(.)4). Participants with stage three or more advanced CKD reported a decrement in the Physical Health Composite score of the SF-12, compared with participants without CKD. CONCLUSION: We found an alarmingly high prevalence of CKD—particularly CKD associated with insulin resistance—in middle-income, urban Bangladeshis.